Poor Sleep Quality Among Adolescents With ASD Is Associated With Depressive Symptoms, Problem Behaviors, and Conflicted Family Relationships. (September 2019) - Phung, Janice N.; Abdullah, Maryam M.; Goldberg, Wendy A.
To better understand correlates of sleep issues for adolescents with autism spectrum disorder (ASD), we conducted two related studies of sleep quality in association with adolescent well-being and family relationships. In Study 1, 28 adolescents with ASD, 27 typically developing (TD) adolescents, and their mothers, participated. Mothers and adolescents independently completed questionnaires about sleep and adolescent functioning. In Study 2, 20 adolescents with ASD and their mothers participated, and actigraphy was used to measure sleep quality. Regression results from Study 1 indicated more daytime sleepiness was associated with more depressive symptoms and more discordant mother–adolescent relationships in the ASD sample. More sleep–wake problems were associated with more depressive symptoms in TD adolescents. In Study 2, more time asleep and poorer sleep efficiency were associated with more depressive symptoms and discordant sibling relationships. These findings suggest that helping adolescents with ASD with their sleep issues may confer benefits in other parts of their lives.